A molybdenum trioxide / reduced graphene oxide composite fiber and its preparation method and application
Molybdenum trioxide/reduced graphene oxide composite fibers were prepared through wet spinning technology, which solved the problems of low conductivity and poor structural stability of molybdenum trioxide, and achieved a composite material with high conductivity and good cycle performance, suitable for lithium ions Battery positive electrode material.
Patent Information
- Application Number
- CN202210907802.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-07-29
AI Technical Summary
In the prior art, when molybdenum trioxide is used as the positive electrode material of lithium-ion batteries, the conductivity is low, the structural stability and cycle stability are poor, and the preparation process is complicated and costly.
Molybdenum trioxide/reduced graphene oxide composite fibers were prepared by wet spinning technology, and the molybdenum trioxide nanoribbon was prepared through hydrothermal reaction, and mixed with the graphene oxide dispersion to form a composite spinning liquid, which was then sprayed into fibers. The reduction process forms composite fibers.
It improves the conductivity and mechanical strength of the composite material, alleviates the structural breakage problem of molybdenum trioxide during charging and discharging, improves its magnification and cycling performance, reduces the resistivity of the material, and ensures the electrical performance of the battery.
Smart Images

Figure CN115161804B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparing composite fibers by wet spinning, and relates to a molybdenum trioxide / reduced graphene oxide composite fiber and a preparation method and application thereof. Background Art
[0002] Realizing efficient electrochemical energy storage is one of the strategies to promote sustainable development in the future. Lithium-ion batteries have the advantages of high specific energy, long cycle life, and no memory points, and have been widely used in portable electronic products. However, one of the limitations of their application is that the specific energy density of the cathode material is low, which cannot match the high specific capacity of the lithium anode of 3860mAh / g. In addition, the electrochemical performance and safety of lithium-ion batteries depend to a large extent on the cathode material. To solve this problem, it is urgent to develop an ultra-high energy density cathode material. Molybdenum trioxide (MoO 3 ) can perform a two-electron reaction at 1-3.25V, with a high theoretical specific energy density of 930Wh / kg. 6 The unique layered nanostructure connected by octahedra provides an effective lithium ion diffusion path, making it promising for use as a positive electrode material for lithium-ion batteries. However, the electrical conductivity of molybdenum trioxide is low, and most of the materials produced by the prior art are nanoparticles, nanosheets or nanofibers, which are small in macroscopic size and have poor electrical conductivity after being made into electrode materials. At the same time, during the charging and discharging process, lithium ions are embedded in the interlayer, which will cause irreversible phase changes in molybdenum trioxide, causing structural fragmentation, resulting in poor rate performance and cycle performance, which seriously limits the practical application of molybdenum trioxide as a positive electrode material for lithium-ion batteries. In the prior art, the electrical conductivity of the material is generally improved by compounding molybdenum trioxide with carbon materials. However, the structural stability and cycle stability of the composite materials obtained by the prior art are still poor. In addition, the preparation process is relatively complicated and the preparation cost is also high. Summary of the invention
[0003] In view of the problems existing in the prior art, the present invention provides a molybdenum trioxide / reduced graphene oxide composite fiber and a preparation method and application thereof, so as to obtain a molybdenum trioxide composite material with stable structure and good conductivity. When the material is used as a positive electrode material of a battery, it has good rate performance and excellent cycle performance.
[0004] The present invention is achieved through the following technical solutions:
[0005] A method for preparing molybdenum trioxide / reduced graphene oxide composite fiber comprises the following steps:
[0006] S1: hydrothermally reacting ammonium molybdate with an aqueous nitric acid solution to obtain molybdenum trioxide nanobelts;
[0007] S2: adding the graphene oxide dispersion into the aqueous solution of the molybdenum trioxide nanobelts, and stirring to obtain a composite spinning solution;
[0008] S3: preparing molybdenum trioxide / graphene oxide composite fibers by spinning the composite spinning solution;
[0009] S4: reducing the molybdenum trioxide / graphene oxide composite fiber to obtain the molybdenum trioxide / reduced graphene oxide composite fiber.
[0010] Preferably, in step S1, the mass ratio of ammonium molybdate to nitric acid is 1:(3-4).
[0011] Preferably, in step S2, the ratio of graphene oxide to molybdenum trioxide nanoribbons is (2-10):(98-90) by weight.
[0012] Preferably, the step S3 specifically comprises: preparing the molybdenum trioxide / graphene oxide composite fiber by spraying the composite spinning solution into a coagulation bath.
[0013] Preferably, the coagulation bath is a calcium chloride aqueous solution or a chitosan hydrochloric acid solution.
[0014] Preferably, the restoration process in step S4 is specifically as follows:
[0015] When step S3 uses a calcium chloride aqueous solution as a coagulation bath, the reduction treatment is performed by at least one of chemical reduction and thermal reduction;
[0016] When the hydrochloric acid solution of chitosan is used as the coagulation bath in step S3, the reduction treatment is performed by chemical reduction or a combination of chemical reduction and thermal reduction.
[0017] Preferably, the chemical reduction process is to mix the molybdenum trioxide / graphene oxide composite fiber with an ascorbic acid solution and allow the mixture to react at a temperature of 80 to 100°C for 30 to 360 minutes; the thermal reduction process is to treat the molybdenum trioxide / graphene oxide composite fiber at 200 to 450°C for 120 to 360 minutes in an Ar gas atmosphere.
[0018] A molybdenum trioxide / reduced graphene oxide composite fiber is prepared by the above method; the length of the composite fiber is greater than 20 cm.
[0019] Application of the above-mentioned molybdenum trioxide / reduced graphene oxide composite fiber in positive electrode materials.
[0020] Application of the above-mentioned positive electrode material in lithium-ion batteries.
[0021] Compared with the prior art, the present invention has the following beneficial technical effects:
[0022] The present invention uses spinning technology to prepare composite fibers of molybdenum trioxide nanobelts and reduced graphene oxide. In the obtained composite fibers, the molybdenum trioxide nanobelts and reduced graphene oxide are closely combined, effectively improving the conductivity of the composite material, and the composite material has good mechanical strength, effectively alleviating the structural fragmentation of molybdenum trioxide caused by the insertion and extraction process of lithium ions when molybdenum trioxide is used as the positive electrode material of lithium ion batteries, improving the structural stability of molybdenum trioxide, and at the same time, during the reduction process, appropriate oxygen defects are introduced into molybdenum trioxide, and the presence of the oxygen defects reduces irreversible lithium ion storage. When the prepared composite material is used as the positive electrode material of a lithium ion battery, it has a higher specific capacity, a stronger rate and a cycle performance, and effectively improves the electrical properties of molybdenum trioxide.
[0023] Furthermore, in terms of mass fractions, the ratio of graphene oxide to molybdenum trioxide nanoribbons is (2-10):(98-90), that is, by adding a small amount of carbon material and combining the method of the present invention, a composite material with excellent performance can be obtained.
[0024] Furthermore, by wet spinning technology, that is, spraying the composite spinning solution into a coagulation bath, the molybdenum trioxide / graphene oxide composite fiber is obtained, and a longer micron fiber can be obtained by a simple method. This method can effectively improve the bonding force between molybdenum trioxide and graphene oxide, thereby improving the structural stability of the final material.
[0025] Furthermore, since chitosan is insoluble in water, when a hydrochloric acid solution of chitosan is used as a coagulation bath, after the preparation of the molybdenum trioxide / graphene oxide composite fiber is completed, a chemical reduction process must be performed during the reduction process. The chemical reducing agent can dissolve the chitosan remaining on the composite fiber, thereby avoiding the residual impurities in the product and improving the purity of the product.
[0026] Furthermore, the molybdenum trioxide / graphene oxide composite fiber was reacted with an ascorbic acid solution at 80-100° C. In addition, the graphene oxide was subjected to a large amount of insulating oxygen-connected sp 3 The carbon atoms are gradually reduced, sp 2 The partial expansion of electrical conductivity has achieved an order of magnitude improvement. In addition, while reducing graphene oxide, an appropriate amount of oxygen defects are introduced into molybdenum trioxide. The structure of the two materials can be controlled in a single step, and the method is simple.
[0027] A molybdenum trioxide / reduced graphene oxide composite fiber is prepared by the wet spinning process of the present invention. By adding a small amount of graphene oxide material, the length of the composite fiber can be greater than 20 cm, which effectively reduces the resistivity of the composite fiber when used as a battery material, thereby ensuring the electrical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 It is a process flow chart of a method for preparing a molybdenum trioxide / reduced graphene oxide composite fiber in the present invention;
[0030] Figure 2 This is a SEM image of the molybdenum trioxide / reduced graphene oxide composite fiber prepared in Example 1 of the present invention;
[0031] Figure 3 The constant current charge and discharge curve of the molybdenum trioxide / reduced graphene oxide composite fiber prepared in Example 1 of the present invention as the positive electrode of a lithium ion battery;
[0032] Figure 4 This is a SEM image of the molybdenum trioxide / reduced graphene oxide composite fiber prepared in Example 2 of the present invention;
[0033] Figure 5 This is the cyclic voltammetry curve of the molybdenum trioxide / reduced graphene oxide composite fiber prepared in Example 3 of the present invention as the positive electrode of a lithium ion battery. DETAILED DESCRIPTION
[0034] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0035] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0036] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0037] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0038] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0039] The present invention provides a method for preparing a molybdenum trioxide / reduced graphene oxide composite fiber, which specifically comprises the following steps:
[0040] S1: Preparation of molybdenum trioxide nanobelts: Take a certain amount of ammonium molybdate and nitric acid, add them to deionized water, and perform hydrothermal synthesis reaction at high temperature and high pressure of 180°C for 24 hours. Then wash the sample several times with deionized water and anhydrous ethanol, dry it to obtain molybdenum trioxide nanobelts, take a certain amount of molybdenum trioxide nanobelts, add them to a certain volume of deionized water, and ultrasonically disperse them to obtain a molybdenum trioxide nanobelt aqueous solution. Among them, ammonium molybdate is tetrahydrated ammonium molybdate or dihydrated ammonium molybdate, and the concentration of nitric acid is 16 mol / L. The drying temperature is 100-120°C, and the drying time is 6-12 hours. The frequency of ultrasonic dispersion is 1000-5000 Hz, and the ultrasonic dispersion time is 10-30 minutes. The mass ratio of ammonium molybdate to nitric acid is 1:(3-4).
[0041] S2: Preparation of molybdenum trioxide / graphene oxide composite spinning solution: viscous graphene oxide dispersion is obtained by centrifugal concentration of graphene oxide, and the graphene dispersion is added to the aqueous solution of molybdenum trioxide nanobelts and stirred to obtain a composite spinning solution. The speed of centrifugal concentration is 11000r / min and the time is 15min. In terms of mass fractions, the ratio of graphene oxide to molybdenum trioxide nanobelts is (2-10): (98-90).
[0042] S3: Preparation of molybdenum trioxide / graphene oxide composite fiber: Put the molybdenum trioxide / graphene oxide composite spinning solution into a spinning tube, extrude it into a coagulation bath at a uniform speed through the nozzle of the spinning tube, perform solvent exchange coagulation, and obtain molybdenum trioxide / graphene oxide composite fiber. The coagulation bath is a calcium chloride aqueous solution or a hydrochloric acid solution of chitosan. The specification of the nozzle is 0.45mm (nozzle outer diameter) * 16mm (nozzle length) ~ 0.5*20mm, and the spinning speed is 5~12mm / min. The concentration of the calcium chloride aqueous solution is 5wt%~15wt%, and the concentration of chitosan in the hydrochloric acid solution of chitosan is 0.5wt%~2wt%.
[0043] S4: Preparation of molybdenum trioxide / reduced graphene oxide composite fiber: The molybdenum trioxide / reduced graphene oxide composite fiber is reduced to obtain the molybdenum trioxide / reduced graphene oxide composite fiber. Specifically, when step S3 uses a calcium chloride aqueous solution as a coagulation bath, the reduction treatment is carried out by at least one of chemical reduction and thermal reduction; when step S3 uses a chitosan hydrochloric acid solution as a coagulation bath, the reduction treatment is carried out by chemical reduction or a combination of chemical reduction and thermal reduction. The chemical reduction process is to mix the molybdenum trioxide / graphene oxide composite fiber with an ascorbic acid solution, and stir the reaction at 80-100°C for 30-60 minutes; the thermal reduction process is to treat the molybdenum trioxide / graphene oxide composite fiber at 200-450°C for 2-6 hours under an Ar gas atmosphere.
[0044] The present invention obtains graphene oxide by treating graphite with a strong acid and a strong oxidant through a modified Hummers method.
[0045] The length of the composite fiber prepared by the method of the present invention is greater than 20 cm, and the mechanical properties are good. As an electrode material, the electrical conductivity and cruising stability of the material are effectively improved, and the electrical properties as a positive electrode of the battery are ensured.
[0046] In addition, the composite fiber is prepared by wet spinning technology and used as the positive electrode material of lithium ion battery. The molybdenum trioxide nanobelt and reduced graphene oxide in the positive electrode material are closely combined, which greatly improves the conductivity of molybdenum trioxide and effectively alleviates the volume expansion of molybdenum trioxide during the charging and discharging process, effectively avoiding the structural fragmentation of the material caused by the lithium ion deintercalation process when molybdenum trioxide is used as the positive electrode material of lithium ion battery. In the reduction process, not only the graphene oxide is reduced to reduced graphene oxide with higher conductivity, but also some oxygen defects are introduced into molybdenum trioxide, which increases the active sites for lithium ion storage, so that the composite fiber has a higher specific capacity, stronger rate and cycle performance, and effectively improves the electrical properties of the material. When the current density of the lithium ion battery is 50mA / g, the reversible lithium storage capacity of the lithium ion battery is 250-400mAh / g.
[0047] The present invention adopts an improved wet spinning preparation process with mild conditions, simple operation and easy large-scale production, and adds graphene oxide to molybdenum trioxide to prepare a spinning solution to prepare molybdenum trioxide / reduced graphene oxide composite fibers, thereby solving the problem of low conductivity of molybdenum oxide, and the synthesized wet-spun fiber structure is uniform and not easy to break, and has good flexibility and structural strength. Compared with the existing technology, the present invention only adds a small amount of graphene oxide to the spinning solution to combine with inorganic molybdenum trioxide to spin ultra-long fibers, and through subsequent reduction treatment, the conductivity of graphene is enhanced and oxygen defects are introduced into molybdenum oxide. The obtained composite fiber is applied to the positive electrode of lithium-ion batteries and has stronger electrochemical properties such as rate and cycle.
[0048] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0049] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0050] Example 1
[0051] A method for preparing molybdenum trioxide / reduced graphene oxide composite fiber comprises the following steps:
[0052] Step 1, preparation of molybdenum trioxide nanobelts: 3.089g of ammonium molybdate tetrahydrate and 15mL of concentrated nitric acid (9.048g) were added to 100mL of deionized water, and the hydrothermal synthesis reaction was carried out at a high temperature and high pressure of 180°C for 24h, and then the sample was washed with deionized water and anhydrous ethanol, and dried at 100°C for 12h to obtain molybdenum trioxide nanobelts. A certain amount of molybdenum trioxide nanobelts was taken, added to a certain volume of deionized water, and dispersed for 30min at an ultrasonic frequency of 1000Hz to obtain a molybdenum trioxide nanobelt aqueous solution with a concentration of 200mg / mL.
[0053] Step 2: Prepare a molybdenum trioxide / graphene oxide composite spinning solution: centrifuge the graphene oxide at a speed of 11000 r / min for 15 min, and obtain a viscous graphene oxide dispersion with a concentration of 8 mg / mL after centrifugal concentration. Take 2.6 mL of the graphene oxide dispersion and add it to 2 mL of the molybdenum trioxide nanobelt aqueous solution and stir to obtain a 95 wt% MoO 3 / rGO composite spinning solution, that is, molybdenum trioxide / graphene oxide composite spinning solution.
[0054] Step 3, preparing molybdenum trioxide / graphene oxide composite fibers: placing the composite spinning solution into a spinning tube, and uniformly extruding it through the nozzle of the spinning tube into a coagulation bath of 0.5wt% chitosan hydrochloric acid aqueous solution, coagulating for 30 minutes, to obtain ultra-long molybdenum trioxide / graphene oxide composite fibers. The nozzle is a disposable sterile syringe with an outer diameter of 0.45mm, a needle length of 16mm, and a spinning speed of 5mm / min.
[0055] Step 4, preparing molybdenum trioxide / reduced graphene oxide composite fibers: placing the molybdenum trioxide / reduced graphene oxide composite fibers in a 0.5 mg / mL ascorbic acid solution at 100°C for 30 min, rinsing with deionized water, air-drying naturally, and then reducing them at 400°C for 6 h in an Ar atmosphere to obtain the composite fibers.
[0056] The molybdenum trioxide / reduced graphene oxide composite fiber prepared by the present invention was assembled into a button battery in a glove box and then subjected to a constant current charge and discharge test. The lithium ion battery prepared in this embodiment has an initial coulombic efficiency of more than 85%, and a reversible lithium storage capacity of 250 mAh / g at a current density of 50 mA / g.
[0057] The SEM image of the molybdenum trioxide / reduced graphene oxide composite fiber prepared in this example is as follows: Figure 2 As shown in the figure, it can be seen that the composite fiber surface has many wrinkles, which are evenly distributed and the components are tightly bound. The constant current charge and discharge of the lithium ion battery prepared in this embodiment is shown in FIG. Figure 1 As shown in the figure, it can be seen that the discharge platform of the composite fiber is around 2.25V. At a current density of 50mA / g, it has an initial specific capacity of 410mAh / g, and the capacity decay is less in subsequent cycles.
[0058] Example 2
[0059] A method for preparing molybdenum trioxide / reduced graphene oxide composite fiber comprises the following steps:
[0060] Step 1, preparation of molybdenum trioxide nanobelts: 3.089g of ammonium molybdate tetrahydrate and 15mL of concentrated nitric acid (9.048g) were added to 100mL of deionized water, and the reaction was carried out under high temperature and high pressure at 180°C for 24h, and then the sample was washed with deionized water and anhydrous ethanol, and dried at 110°C for 10h to obtain molybdenum trioxide nanobelts. A certain amount of molybdenum trioxide nanobelts was taken, added to a certain volume of deionized water, and dispersed for 24min at an ultrasonic frequency of 1500Hz to obtain a molybdenum trioxide nanobelt aqueous solution with a concentration of 200mg / mL.
[0061] Step 2: Prepare a molybdenum trioxide / graphene oxide composite spinning solution: centrifuge the graphene oxide at a speed of 11000 r / min for 15 min, and obtain a viscous graphene oxide dispersion with a concentration of 8 mg / mL after centrifugal concentration. Take 2.6 mL of the graphene oxide dispersion and add it to 2 mL of the molybdenum trioxide nanobelt aqueous solution and stir to obtain a 95 wt% MoO 3 / rGO composite spinning solution, that is, molybdenum trioxide / graphene oxide composite spinning solution.
[0062] Step 3, preparing molybdenum trioxide / graphene oxide composite fibers: placing the composite spinning solution into a spinning tube, extruding it through the nozzle of the spinning tube at a uniform speed into a 15wt% calcium chloride coagulation bath, and coagulating for 30 minutes to obtain ultra-long molybdenum trioxide / graphene oxide composite fibers. The specification of the nozzle is 0.5*20mm, and the spinning speed is 7mm / min.
[0063] Step 4, preparing molybdenum trioxide / reduced graphene oxide composite fibers: placing the molybdenum trioxide / reduced graphene oxide composite fibers in a 0.5 mg / mL ascorbic acid vitamin C solution at 90°C for reduction for 40 min, rinsing with deionized water, air-drying naturally, and then reducing them at 300°C for 5 h in a helium atmosphere to obtain the composite fibers.
[0064] The length of the molybdenum trioxide / reduced graphene oxide composite fiber prepared in this embodiment is 25 cm. After the battery is assembled in a glove box, a constant current charge and discharge test is performed, and the conductivity is significantly improved.
[0065] The SEM image of a molybdenum trioxide / reduced graphene oxide composite fiber prepared by the wet spinning preparation method described in this embodiment is as follows: Figure 4 shown.
[0066] Example 3
[0067] A method for preparing molybdenum trioxide / reduced graphene oxide composite fiber comprises the following steps:
[0068] Step 1, preparation of molybdenum trioxide nanobelts: 3.089g of ammonium molybdate dihydrate and 15mL of concentrated nitric acid (9.048g) were added to 100mL of deionized water, and the reaction was carried out under high temperature and high pressure at 180°C for 24h, and then the sample was washed with deionized water and anhydrous ethanol, and dried at 120°C for 6h to obtain molybdenum trioxide nanobelts. A certain amount of molybdenum trioxide nanobelts was taken, added to a certain volume of deionized water, and dispersed for 22min at an ultrasonic frequency of 2000Hz to obtain a molybdenum trioxide nanobelt aqueous solution with a concentration of 200mg / mL.
[0069] Step 2: Prepare a molybdenum trioxide / graphene oxide composite spinning solution: centrifuge the graphene oxide at a speed of 11000 r / min for 15 min, and obtain a viscous graphene oxide dispersion with a concentration of 8 mg / mL after centrifugal concentration. Take 2.6 mL of the graphene oxide dispersion and add it to 2 mL of the molybdenum trioxide nanobelt aqueous solution and stir to obtain a 95 wt% MoO 3 / rGO composite spinning solution, that is, molybdenum trioxide / graphene oxide composite spinning solution.
[0070] Step 3, preparing molybdenum trioxide / graphene oxide composite fibers: placing the composite spinning solution into a spinning tube, and uniformly extruding it through the nozzle of the spinning tube into a coagulation bath of a 1wt% chitosan hydrochloric acid aqueous solution, coagulating for 30 minutes, to obtain ultra-long molybdenum trioxide / graphene oxide composite fibers. The specification of the nozzle is 0.45*18mm, and the spinning speed is 10mm / min.
[0071] Step 4, preparing molybdenum trioxide / reduced graphene oxide composite fibers: placing the molybdenum trioxide / reduced graphene oxide composite fibers in a 0.5 mg / mL ascorbic acid solution at 80°C for 30 min, rinsing with deionized water, air-drying naturally, and then reducing them at 300°C for 4 h in an Ar atmosphere to obtain the composite fibers.
[0072] The length of the molybdenum trioxide / reduced graphene oxide composite fiber prepared in this embodiment is 25 cm. After battery assembly in a glove box, constant current charge and discharge test and cycle performance test are carried out. The cyclic voltammetry test curve is shown in FIG. Figure 5 As shown in the figure, when the scan rate in the cyclic voltammetry curve is 0.2mV / s, the redox peak is Figure 3 The charge-discharge platform of the constant current charge-discharge curve corresponds well. At the same time, when different scan rates are used, the shape of the voltammetric curve of the composite fiber positive electrode does not change, indicating that its rate performance is good.
[0073] Example 4
[0074] The difference between this embodiment and embodiment 1 is that the mass ratio of ammonium molybdate to nitric acid in step 1 is 1:3.5, and after the reaction is completed, the drying temperature is 105°C and the drying time is 12h. The frequency in the ultrasonic dispersion process is 2500Hz, and the ultrasonic dispersion time is 26min; in step 2, the ratio of graphene oxide to molybdenum trioxide nanobelt is 2:98 by mass fraction; in step 3, the coagulation bath is 8wt% calcium chloride aqueous solution, and the spinning speed is 10mm / min; the reduction process in step 4 is specifically as follows: the molybdenum trioxide / reduced graphene oxide composite fiber is placed in a 0.5mg / mL ascorbic acid solution at 80°C for 60min, rinsed with deionized water, naturally air-dried, and then reduced at 300°C for 3h in an Ar gas atmosphere to obtain the composite fiber. The length of the molybdenum trioxide / reduced graphene oxide composite fiber prepared in this embodiment is 22 cm. After the molybdenum trioxide / reduced graphene oxide composite fiber prepared in this embodiment is assembled into a lithium ion battery, the reversible lithium storage capacity of the lithium ion battery is 230 mAh / g when the current density is 50 mA / g.
[0075] Example 5
[0076] The difference between this embodiment and embodiment 1 is that the mass ratio of ammonium molybdate to nitric acid in step 1 is 1:4, and after the reaction is completed, the drying temperature is 115°C and the drying time is 10h. The frequency in the ultrasonic dispersion process is 3000Hz, and the ultrasonic dispersion time is 20min; in step 2, the ratio of graphene oxide to molybdenum trioxide nanobelt is 5:95 by mass fraction; in step 3, the coagulation bath is a 5wt% calcium chloride aqueous solution, and the spinning speed is 12mm / min; the reduction process in step 4 is specifically as follows: the molybdenum trioxide / reduced graphene oxide composite fiber is placed in a 0.5mg / mL ascorbic acid solution at 80°C for 60min, rinsed with deionized water, naturally air-dried, and then reduced at 200°C for 6h in an Ar gas atmosphere to obtain the composite fiber. The length of the molybdenum trioxide / reduced graphene oxide composite fiber prepared in this embodiment is 25 cm. After the molybdenum trioxide / reduced graphene oxide composite fiber prepared in this embodiment is assembled into a lithium ion battery, the reversible lithium storage capacity of the lithium ion battery is 235 mAh / g when the current density is 50 mA / g.
[0077] Example 6
[0078] The difference between this embodiment and embodiment 1 is that the mass ratio of ammonium molybdate to nitric acid in step 1 is 1:4, and after the reaction is completed, the drying temperature is 120°C and the drying time is 12h. The frequency in the ultrasonic dispersion process is 5000Hz, and the ultrasonic dispersion time is 10min; in step 2, the ratio of graphene oxide to molybdenum trioxide nanobelt is 7:93 by mass fraction; in step 3, the coagulation bath is a 15wt% calcium chloride aqueous solution, and the spinning speed is 12mm / min; the reduction process in step 4 is specifically: placing the molybdenum trioxide / reduced graphene oxide composite fiber under an Ar gas atmosphere, and reducing it at 200°C for 6h to obtain the composite fiber. The length of the molybdenum trioxide / reduced graphene oxide composite fiber obtained in this embodiment is 27cm. After the molybdenum trioxide / reduced graphene oxide composite fiber obtained in this embodiment is assembled into a lithium ion battery, the reversible lithium storage capacity of the lithium ion battery is 300mAh / g when the current density is 50mA / g.
[0079] Example 7
[0080] The difference between this embodiment and embodiment 6 is that in step 2, the ratio of graphene oxide to molybdenum trioxide nanobelt is 10:90 by weight; in step 3, the coagulation bath is a 15wt% calcium chloride aqueous solution, and the spinning speed is 12mm / min; the reduction process in step 4 is specifically as follows: the molybdenum trioxide / reduced graphene oxide composite fiber is placed in a 0.5mg / mL ascorbic acid solution at 80°C for reduction for 60min, rinsed with deionized water, and naturally air-dried to obtain the composite fiber. The length of the molybdenum trioxide / reduced graphene oxide composite fiber obtained in this embodiment is 26cm. After the molybdenum trioxide / reduced graphene oxide composite fiber obtained in this embodiment is assembled into a lithium ion battery, the lithium ion battery has a reversible lithium storage capacity of 320mAh / g when the current density is 50mA / g.
[0081] Example 8
[0082] The difference between this embodiment and embodiment 6 is that in step 2, the ratio of graphene oxide to molybdenum trioxide nanobelt is 10:90 by weight; in step 3, the coagulation bath is a hydrochloric acid solution of 2wt% chitosan, and the spinning speed is 12mm / min; the reduction process in step 4 is specifically as follows: the molybdenum trioxide / reduced graphene oxide composite fiber is placed in a 0.5mg / mL ascorbic acid solution at 80°C for 60min, rinsed with deionized water, and naturally air-dried to obtain the composite fiber. The length of the molybdenum trioxide / reduced graphene oxide composite fiber obtained in this embodiment is 30cm. After the molybdenum trioxide / reduced graphene oxide composite fiber obtained in this embodiment is assembled into a lithium ion battery, the lithium ion battery has a reversible lithium storage capacity of 350mAh / g when the current density is 50mA / g.
[0083] Example 9
[0084] The difference between this embodiment and embodiment 8 is that the coagulation bath in step 3 is a hydrochloric acid solution of 0.5wt% chitosan; the reduction process in step 4 is specifically as follows: the molybdenum trioxide / reduced graphene oxide composite fiber is placed in a 0.5mg / mL ascorbic acid solution for reduction at 80°C for 60min, rinsed with deionized water, naturally air-dried, and then reduced at 400°C for 6h in a helium atmosphere to obtain the composite fiber. The length of the molybdenum trioxide / reduced graphene oxide composite fiber obtained in this embodiment is 29cm. After the molybdenum trioxide / reduced graphene oxide composite fiber obtained in this embodiment is assembled into a lithium ion battery, the reversible lithium storage capacity of the lithium ion battery is 360mAh / g when the current density is 50mA / g.
[0085] Example 10
[0086] The difference between this embodiment and embodiment 9 is that the coagulation bath in step 3 is a hydrochloric acid solution of 1.5wt% chitosan; the reduction process in step 4 is specifically as follows: the molybdenum trioxide / reduced graphene oxide composite fiber is placed in a 0.5mg / mL ascorbic acid solution for reduction at 90°C for 40min, rinsed with deionized water, naturally air-dried, and then reduced at 350°C for 6h in a helium atmosphere to obtain the composite fiber. The length of the molybdenum trioxide / reduced graphene oxide composite fiber obtained in this embodiment is 30cm. After the molybdenum trioxide / reduced graphene oxide composite fiber obtained in this embodiment is assembled into a lithium ion battery, the lithium ion battery has a reversible lithium storage capacity of 400mAh / g when the current density is 50mA / g.
[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing molybdenum trioxide / reduced graphene oxide composite fiber, characterized in that: The following steps are involved: S1: hydrothermally reacting ammonium molybdate with an aqueous nitric acid solution to obtain molybdenum trioxide nanobelts; S2: adding the graphene oxide dispersion into the aqueous solution of the molybdenum trioxide nanobelts, and stirring to obtain a composite spinning solution; S3: preparing molybdenum trioxide / graphene oxide composite fibers by spinning the composite spinning solution; S4: reducing the molybdenum trioxide / graphene oxide composite fiber to obtain the molybdenum trioxide / reduced graphene oxide composite fiber; In the step S2, the ratio of graphene oxide to molybdenum trioxide nanoribbons is (2-10):(98-90) by weight. The step S3 specifically comprises: preparing the molybdenum trioxide / graphene oxide composite fiber by spraying the composite spinning solution into a coagulation bath; The coagulation bath is a calcium chloride aqueous solution or a chitosan hydrochloric acid solution; The spinning speed is 5-12 mm / min; The length of the molybdenum trioxide / reduced graphene oxide composite fiber is greater than 20 cm; In the step S1, the mass ratio of ammonium molybdate to nitric acid is 1:(3-4).
2. The method for preparing a molybdenum trioxide / reduced graphene oxide composite fiber according to claim 1, characterized in that: The restoration process in step S4 is specifically as follows: When step S3 uses a calcium chloride aqueous solution as a coagulation bath, the reduction treatment is performed by at least one of chemical reduction and thermal reduction; When the hydrochloric acid solution of chitosan is used as the coagulation bath in step S3, the reduction treatment is performed by chemical reduction or a combination of chemical reduction and thermal reduction.
3. The method for preparing a molybdenum trioxide / reduced graphene oxide composite fiber according to claim 2, characterized in that: The chemical reduction process is to mix the molybdenum trioxide / graphene oxide composite fiber with an ascorbic acid solution and let it stand for reaction at a temperature of 80 to 100° C. for 30 to 360 minutes; the thermal reduction process is to treat the molybdenum trioxide / graphene oxide composite fiber at 200 to 450° C. for 120 to 360 minutes in an Ar gas atmosphere.
4. A molybdenum trioxide / reduced graphene oxide composite fiber, characterized in that: Prepared by the method described in any one of claims 1 to 3; the length of the molybdenum trioxide / reduced graphene oxide composite fiber is greater than 20 cm.
5. Use of the molybdenum trioxide / reduced graphene oxide composite fiber described in claim 4 in positive electrode materials.
6. Use of the positive electrode material described in claim 5 in a lithium ion battery.
Citation Information
Patent Citations
Method for preparing graphene fibers, graphene fibers, yarns, electric component, and electric conductor
CN110016735A